Efficacy and safety of Sangbaipi Decoction in patients with acute exacerbation of chronic obstructive pulmonary disease: A protocol for systematic review and meta analysis. Issue 44 (30th October 2020) - Li, Jiazhou; Jiang, Junlin; Jing, Chunxiang; Zheng, Wenjiang; Pan, Huashan
Abstract: Background: Chinese medicine Sangbaipi decoction is extensively applied to the therapy of acute exacerbation of chronic obstructive pulmonary disease (AECOPD) in China. However, owing to the low quality, small sample size, and methodological heterogeneity of these studies, this conclusion is not convincing. Consequently, it is necessary to systematically evaluate the clinical efficacy and safety of Sangbaipi Decoction in the treatment of AECOPD patients, and provide high-quality evidence for its clinical application. Methods: We will follow the preferred reporting items for systematic review and meta-analysis (PRISMA) for reporting the results of the review in this study. We will utilize the Review Manage software V5.3.0 (The Nordic Cochrane Center, The Cochrane Collaboration, 2014, Copenhagen, Denmark) to assess the risk of bias and visualize the results. We will use Stata software (version 15.0, StataCorp, College Station, TX) to perform the meta-analysis. Ethics and dissemination: This study is a systematic review and meta-analysis protocol of Sangbaipi decoction on AECOPD, participants were not recruited and data were not collected from participants, so ethical ratification is not required. Results: This study will provide high-quality synthesis of the effectiveness and safety of Sangbaipi decoction for AECOPD. Upon completion, the results will be submitted to a peer-reviewed journal. Conclusion: The efficacy and safety assessment of Sangbaipi decoction for AECOPD will be supported by this protocol. Registration number: PROSPERO CRD 42019138405.